2006
DOI: 10.1055/s-2005-865817
|View full text |Cite
|
Sign up to set email alerts
|

Increased Susceptibility to Plasma Lipid Peroxidation in Untrained Subjects after an Extreme Mountain Bike Challenge at Moderate Altitude

Abstract: The purpose of this study was to determine whether acute strenuous physical exercise, partially performed under moderate altitude, influences the susceptibility of plasma lipids to peroxidation. Eleven male amateur cyclists took part in a 95-km mountain bike challenge with a cumulative altitude difference of 2340 m. Blood samples were obtained before and immediately after the race in order to determine plasma lipid and lipoprotein concentrations, and to assess the susceptibility of the former to peroxidation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Total cholesterol levels reduced from as little as 0.5% to 30% in five out of eight studies [6,10,[26][27][28], although one study [29] reported a significant increase of 4.5 % at 4800m and 4.3% at 3000m.…”
Section: Cholesterol Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total cholesterol levels reduced from as little as 0.5% to 30% in five out of eight studies [6,10,[26][27][28], although one study [29] reported a significant increase of 4.5 % at 4800m and 4.3% at 3000m.…”
Section: Cholesterol Levelsmentioning
confidence: 99%
“…While epidemiology studies have reported increased total cholesterol among high altitude dwellers [40], in this review, studies indicated that hypoxic training was able to reduce total cholesterol [6,10,[26][27][28], and this included subjects with obesity and metabolic syndrome. One striking difference between those studies and epidemiology is the inclusion of an exercise regime with concurrent hypoxic training, which would affect findings.…”
Section: Cholesterol Levelsmentioning
confidence: 99%
“…The exercise-induced production of reactive oxygen species is well documented in healthy sedentary (Jammesa, Steinberg, Brégeon, & Delliaux, 2004), trained (Ji, Gomez-Cabrera, & Viñ a, 2006), and non-trained individuals (Ruiz, Ortega, Castillo, Gutierrez, & Agil, 2006). Exercise increases oxygen uptake and almost 2% of the oxygen may be converted to reactive oxygen species.…”
Section: Introductionmentioning
confidence: 99%
“…However, Hue et al [9] found that resting thermoregulatory and some haematological variables were unaffected during a 9-day cycling stage race, and Vogt et al [28] found that professional cyclists are not in negative energy balance during intensive pre-season training. In less-trained subjects, Ruiz et al [23] found that a 95-km mountain bike competition held at moderate altitude increased the susceptibility of plasma lipids to peroxidation by about 72%. Such differences between worldclass and recreational cyclists might of course be explained by genetic factors.…”
mentioning
confidence: 99%